Find HCF LCM of the following monomials:

 1)  \ \  ab^2 \ \ and\ \  a^2 b    

     HCF = ab    

     LCM = a^2 b^2    

\\  

 2)  \ \  a^3 b^2 \ \ and\ \   a^2 b^4    

     HCM = a^2 b^2    

     LCM = a^2 b^4    

\\  

 3) \ \    4x^2 y^3 \ \ and\ \   6xy^4    

     HCF = 2xy^3    

     LCM = 12x^2  y^4    

\\  

  4) \ \   6abc \ \ and\ \   9bc^2 d    

     HCM = 3bc    

     LCM = 18abc^2 d    

\\  

 5) \ \    2m^2 n^3, \ \   3mn^2 \ \ and\ \   4m^3 n    

     HCM = mn    

     LCM = 12m^3  n^3    

\\  

 6) \ \    5x^3 y^2, 10x^2 z^2 \ \ and\ \   15y^3 z^3    

     HCF = 5x^2    

     LCM = 30x^3 y^3 z^3    

\\  m34x

  7) \ \   6x^2 y^2  z^4, 9x^4  y^5 z \ \ and\ \   12xy^2 z^3    

     HCF = 3xy^2 z    

     LCM= 36x^4 y^5 z^4    

\\  

Find HCF and LCM of following polynomials

 1) \ \    x^2-a^2 \ \ and\ \   x^2-ax    

We have

      x^2-a^2=(x-a)(x+a)=x^2-ax x(x-a)    

     Therefore    

     HCF = (x-a)    

     LCM= x (x-a)(x+a)    

\\  

 2)  \ \  9a^2-16b^2 \ \ and\ \   6a^2+8ab    

We have

     9a^2-16b^2=(3a-4b)(3a+4b)    

     6a^2+8ab=2a(3a+4b)    

Therefore

     HCF =(3a+4b)    

     LCM = 2a(3a+4b)(3a-4b)    

\\  

 3)  \ \  x^3-16x \ \ and\ \   x^3+2x^2-24x    

We have

      x^3-16x=x(x-4)(x+4)    

     x^3+2x^2-24x=x (x^2+2x-24)=x(x+6)(x-4)    

     HCF = x(x-4)    

     LCM = x(x-4)(x+6)(x+4)    

\\  

 4) \ \    x^2+x-12 and x^2-6x+9    

We have

      x^2+x-12=(x+4)(x-3)    

     x^2-6x+9=(x-3)(x-3)    

     HCF= (x-3)    

     LCM = (x-3)(x-3)(x+4)    

\\  

  5) \ \   x^2-36 \ \ and\ \   2x^2-15x+18    

We have

      x^2-36=(x-6)(x+6)    

     2x^2-15x+18= 2x^2-12x-3x+18= 2x(x-6)-3(x-6)= (2x-3)(x-6)    

Therefore

     HCF = (x-6)    

     LCM = (x-6)(2x-3)(x+6)    

\\  

 6) \ \    6a^2 b (a^2-b^2 ) \ \ and\ \   4ab^2 (a+b)^2    

 We have

     6a^2 b (a^2-b^2 )= 6a^2 b (a-b)(a+b)    

     4ab^2 (a+b)^2=4a^2 b^2 (a+b)(a-b)    

Therefore

     HCF=2ab(a+b)    

     LCM=12a^2 b^2 (a+b)(a-b)    

\\  

 7)\ \    xy+y^2, xy-y^2 \ \ and\ \   x^2  y^2-y^4    

We have

     xy+y^2=y(x+y)    

     xy-y^2=y(x-y)    

     x^2 y^2-y^4=y^2 (x^2-y^2 )= y^2 (x-y)(x+y)    

     HCF = y    

     LCM = y^2 (x-y)(x+y)    

\\  

 8)\ \   x^2+3x, x^2+5x+6 \ \ and\ \   x^2+4x+3    

We have

     x^2+3x=x(x+3)    

     x^2+5x+6=(x+12)(x+3)    

     x^2+4x+3=(x+1)(x+3)    

Therefore

     HCF = (x+3)    

     LCM= x(x+1)(x+2)(x+3)    

\\  

  9)\ \   x^2+3x-4, x^3-2x^2+x \ \ and\ \   x^2+2x-3    

We have

      x^2+3x-4=(x+4)(x-1)    

     x^3-2x^2+x=x(x^2-2x+1)=x(2-1)(x-1)    

     x^2+2x-3=(x+3)(x-1)    

Therefore

     HCF =(x-1)    

     LCM = x(x+3)(x-1)(x+4)(x-1)    

\\  

 10)\ \    x^2-16, x^2-3x-28 \ \ and\ \   x^2-11x+28    

We have

     x^2-16=(x-4)(x+4)    

     x^2-3x-28=(x-7)(x+4)    

     x^2-11x+28=(x-7)(x-4)    

Therefore

     HCF = 1    

     LCM = (x-7)(x-4)(x+4)    

\\  

 11)  \ \  12x^2-75, 4x^2-20x+25 \ \ and\ \   6x^2-13x-5    

We have

      12x^2-75=3(4x^2-25)=3(2x-5)(2x+5)    

     4x^2-20x+25=(2x-5)(2x-5)    

     6x^2-13x-5=(2x-5)(3x-1)    

Therefore

     HCF = (2x-5)    

     LCM = 3(2x-5)(3x-1)(2x-5)(2x+5)    

\\  

 12)  \ \  2a^2+a-6, (2a-3)^2 \ \ and\ \   (4a^2-9)    

m36xWe have

     2a^2+a-6= 2a^2+4a-3a-6=2a(a+2)-3(a+2)=(a+2)(2a+3)    

     (2a-3)^2=(2a-3)(2a-3)    

     (4a^2-9)=(2a-3)(2a+3)    

Therefore

     HCF = (2a-3)    

     LCM = (2a-3)(2a+3)(2a-3)(a+2)    

\\  

 13)   \ \  4m^4 n (m^4-n^4 ), 6m^3 n^2 (m^2+2mn-3n^2 ), 24m^2 n^3 (m^3+m^2 n+mn^2+n^3)    

We have

      4m^4 n(m^4-n^4 )= 4m^4 n (m^2-n^2 )(m^2+n^2 )=4m^4 n (m-n)(m+n)(m^2+n^2 )    

     6m^3 n^2 (m^2+2mn-3n^2)= 6m^3 n^2 (m+3m)(m-n)    

     24m^2 n^3 (m^3+m^2 n+mn^2+n^3 )=24mn^2 n^3 (m+n)(m^2+n^2)    

Therefore

     HCF = 2m^2 n    

     LCM = 24m^4 n^3 (m-n)(m+n)(m+3n)(m^2+n^2)    

Advertisements